To Study Effect of Modified Constraint Induced Movement Therapy on Hand Function in Patients with Chronic Stroke- Case Report - Meghna Prabhu (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background and aims The following study was conducted to study the effect of modified constraint induced movement therapy on hand function in patients with chronic stroke. Hand function is affected due to weakness, sensory loss, abnormal tone, unilateral neglect. Modified constraint induced movement therapy is known to induce neural plasticity which helps improve functional ability. Methods A descriptive case study was carried out on 2 patients screened from the community and selected through purposive sampling. They were given mCIMT for a duration of 2hrs/ 5 days a week for 3 weeks along with conventional upper limb exs. The unaffected hand was constrained and the affected hand was engaged in functional activities. The patients were also instructed to wear the restraint for 3 hours unsupervised and maintain a log of the activities. MAL and JTHFT were used as pre and post outcome measures. Results For JTHFT, the one-tailed p-value for grip is 0.02 for subject 1 and p<0.006 for subject 2 which is statistically significant at 5% level of significance. The p-value for writing is p<0.03 for subject 1 and p<0.02 for subject 2 which is statistically significant. The p-value for the other components for all subjects is p>0.1 and hence it is not statistically significant. For MAL, The one-tailed p-value calculated for each subject for Motor Activity Log of the Amount scale and Quality of Movement scale is p<0.001 which is very significant.